Problems and ways to improve the organization of the work of the university dental center based on the results of a sociological survey of dentists. - Chopchik, V. D. (Medicni Perspektivi, 2019)
The purpose of this study was to analyze the state, problems and ways to improve the organization of the work of the Dental Medical Center (SMC) of A.A. Bogomolets National Medical University on the basis of a sociological survey of dentists. A sociological survey was conducted among 101 dentists of DMC. A specially designed questionnaire was used. According to the dentists’ opinion, the main directions for improving the organization of the SMC are the introduction of mechanisms for the economic motivation of staff (71.3±4.5%); modern dental technologies (82.2±3.8%); equipping the center with modern medical and diagnostic equipment (88.1±3.2%); improving the quality of postgraduate training of dentists (96.0±1.9%); introduction of a system for monitoring the quality of medical care (58.4±4.9%); improving the efficiency and quality of dental services through program initiatives of the departments of DMC (52.5±5.0%); an increase of the economic and legal independence of the dental center (76.2±4.2%); organizational, academic and financial autonomy of the center (88.1±3.2%); introduction of public-private partnership mechanisms in the DMC (75.2±4.3%). The conducted sociological research allowed to establish that the main parameters of the organization and management of the DMC do not correspond to the economic realities of time and require modernization, as well as determining the main directions of development of the DMC.